THE IMPORTANCE OF PLAYING IN CHILDHOOD EDUCATION - Boni, Cinara; Zancan, Sinara; Piccoli Diehl, Rosicler; Larissa da Silva Flores, Juliane; Raquel Faccin, Tânia; Possa Moreschi, Margarida; Scalcon dos Santos de Lima, Marta (Revista Gênero e Interdisciplinaridade, 2023)
Playing, in addition to being a source of entertainment and something essential in Early Childhood Education, encourages the full development of the child, because playing they begin to express their personality and emotions. Playing as a pedagogical proposal aims to show that stimulated games are capable of contributing to the physical, cognitive, motor and emotional development of the child. Playing is a fundamental moment for the child, because it is at this stage that the subject is formed, developing his creativity in his social context in which he is inserted. Therefore, providing opportunities for playful experiences in order to create the possibility of enchantment, provides learning in their daily lives. Playing in early childhood education should not be considered only superficial, worthless games, because in playing, fantasies forces wake up and live, which in turn, has a direct action on the formation and structuring of the child’s thinking. Playing constitutes the most important and decisive basic form of the human being, it makes the child’s creative forces blossom and activate. Children’s fantasy needs, in order to be able to develop through the active and curious handling of the material, that the child has the opportunity to experience in the world, the forms and the quality of everything that is around him